2018
DOI: 10.1017/jmo.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

How personal-life inclusion affects Chinese turnover intention? A moderated mediation model of work interference with family and perceived family demands

Abstract: While an increasing number of studies focus on the positive effects of Chinese supervisor–subordinate guanxi on its focal parties, little research has examined in what situations guanxi may instead cause negative impacts on these individuals. Drawing on conservation of resources theory, the objectives of this study is to identify how the culturally remarkable aspect of supervisor–subordinate guanxi – personal-life inclusion – may cause ‘burden’ for Chinese employees and to reveal the moderated mediation mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Drawing on social exchange theory, interactions between supervisors and subordinates involve the exchange of resources, friendliness, and trust. Previous researchers have shown that S-s guanxi is related to a wide range of subordinates'work-related outcomes, such as organizational commitment, job satisfaction, turnover intention, organizational citizenship behavior (OCB), task performance, career development, and intention to stay [16,17]. In China, employees always respect authorities; therefore, good relationships with supervisors ensure that employees make things happen at work [18].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Drawing on social exchange theory, interactions between supervisors and subordinates involve the exchange of resources, friendliness, and trust. Previous researchers have shown that S-s guanxi is related to a wide range of subordinates'work-related outcomes, such as organizational commitment, job satisfaction, turnover intention, organizational citizenship behavior (OCB), task performance, career development, and intention to stay [16,17]. In China, employees always respect authorities; therefore, good relationships with supervisors ensure that employees make things happen at work [18].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…According to the Amway Global Entrepreneurship Report, the Chinese government has provided effective support for startups, and enthusiasm for entrepreneurship has improved rapidly. Management research in the Chinese context has also attracted the attention of many scholars (e.g., Ren & Chen, 2021;Wang, Yang, & Zhang, 2021;Zhang, Ji, Anwar, Li, & Fu, 2020). Jiangsu, Zhejiang, and Shanghai have the strongest entrepreneurial atmosphere, and their economic development is very close to that of Western countries (Yeh & Xu, 2010).…”
Section: Sample and Data Collectionmentioning
confidence: 99%